Técnicas metodológicas empleadas en la enseñanza del inglés en Educación Infantil. Estudio de caso. - Rodríguez López, Beatriz (Didáctica. Lengua y Literatura, 2004)
This article tries to describe the methodological techniques used by a group of teachers to teach English at Infants School at the «Colegios Rurales Agrupados del Baixo Miño» in the South of Galicia.
Keywords: Teaching English Methodological techniques Infants School